تحليل رسائل الماجستير المجازة في جامعة حضرموت خلال الفترة من 2004-2018 وفقا لبعض المتغيرات - السفياني، هلال محمد علي سيف; الخطيب، خليل محمد مطهر (جامعة القلم للعلوم الإنسانية والتطبيقية, 2021)
تحددت أهداف البحث في تحليل رسائل الماجستير المجازة في جامعة حضرموت للفترة: (2004 - 2018 م)، وفقا لمتغيرات: (الكلية، نوع الكلية، القسم، التخصص، نوع الباحث، سنة الإجازة، لغة البحث، نوع بيانات البحث، عدد كلمات العنوان)، واعتمد البحث على المنهج الوصفي، باستخدام أسلوب تحليل المضمون، وخلصت النتائج إلى أن عدد رسائل الماجستير المجازة في جامعة حضرموت للفترة (2004 - 2018م) حوالي (360) رسالة ماجستير في (20) تخصصا علميا، معظمها أبحاث ميدانية، توزعت بين الكليات بنسبة: (71.9%) نظرية، و(28.1%) تطبيقية، شارك في إجرائها (68.9%) من الذكور، و(31.1%) من الإناث، وكتبت بلغتين: منها (81.1%) باللغة العربية، و(18.9%) باللغة الإنجليزية. وجاءت كلية الآداب في مقدمة الكليات إجازة لرسائل الماجستير، تليها التربية، ثم الطب، ثم العلوم الإدارية، ثم البيئية والأحياء البحرية، ثم كليتي البنات والعلوم، وبلغ المتوسط المرجح للرسائل المجازة كل عام (3) رسائل في كل تخصص، ومثلت الرسائل المجازة خلال الخمس السنوات الأولى ما نسبته (16%)، وفي الخمس السنوات التالية (31%)، وفي الخمس السنوات الأخيرة (53%)، كما أن عدد كلمات العناوين الأكثر شيوعا هي الأقل من (12) كلمة، تليها (12 - 15) كلمة.
This article aims to analyze the Master Theses approved by Hadramout University during (2004-2018) according to the following variables: Faculty, type of Faculty, Department, Specialization, type of researcher, year of approval, research language, research data type, and the number of words of the title. The study employs the descriptive approach using the method of content analysis. The study concludes that the number of the Master Theses approved by Hadramout University during (2008 2018) is about (360) in (20) scientific specializations. Most of these Theses are field researches, which are categorized into theoretical (71.9%) and applied (28.1%) researches. They were conducted by males (68.9%) and females (31.1). They were written in Arabic (81.1%) and English (18.9%) Faculty of Arts ranked first with the most approved Master Theses, followed by Faculty of Education, then Faculty of Medicine. Faculty of Environmental Science and Marine Biology followed by Faculty of Administrative Sciences, and finally Faculty of Girls and Sciences. The average of the approved Theses is (3) every year in each specialization. The Theses approved in the first five years represent (16%), and (31%) in the following five years. In the last five years, the approved Theses represent (53%). The most commonly written words of titles were less than (12) followed by the number (12-15) words.
Keywords: التعليم الجامعي -- طلبة الدراسات العليا -- رسائل الماجستير -- جامعة حضرموت -- اليمن